Tuesdays With Morrie (2009)
Colour Clar Doyle (director & lighting design), Jim Hoskins (set design), Sean Panting (sound design), Jennifer Nakashima (stage manager), Jason Card and Ted Quinlan (producers). Starring Jason Card and Jerry Doyle Beothuck Street Players